Correlation between the Joint Roughness Coefficient and Rock Joint Statistical Parameters at Different Sampling Intervals. (29th July 2019) - Huang, Man; Xia, Cia-chu; Sha, Peng; Ma, Cheng-rong; Du, Shi-gui
Abstract : Joint roughness coefficient (JRC) is a major factor that affects the mechanical properties of rock joints. Statistical methods that are used to calculate the JRC increasingly depend on a sampling interval (Δ x ). The variation rules of fitting parameters a, b, and b / a at different Δ x values were analyzed on the basis of the relationship between the JRC and statistical parameter Z 2 . The relationship between the fitting parameters a and b was deduced in accordance with the ten standard profiles proposed by Barton. Empirical formulas for the JRC, Z 2, and Δ x were also established. The estimation accuracy of the JRC was the highest in the analysis of Δ x values within 0.1–5.0 mm. JRC tests were conducted through inverse value comparative analysis. Results showed that the outcome calculated using the general formula and the JRC inverse values demonstrate improved agreement and verify the rationality of the general formula. The proposed formula can perform rapid and simple JRC calculation within the Δ x range of 0.1–5.0 mm using Z 2, thereby indicating favorable application prospects.